THU0102 PATIENT DISEASE TRAJECTORIES IN BARICITINIB-TREATED PATIENTS WITH RHEUMATOID ARTHRITIS AND INADEQUATE RESPONSE TO METHOTREXATE. (June 2019) - Taylor, Peter C.; Emery, Paul; Weinblatt, Michael E.; Mysler, Eduardo; Rubbert-Roth, Andrea; Jia, Bochao; Sun, Luna; Liu, Yushi; Chen, Yun-Fei; Cardoso, Anabela; Tanaka, Yoshiya
Abstract : Background: In RA-BEAM phase 3 study, baricitinib (bari) 4mg demonstrated clinical efficacy in patients (pts) with rheumatoid arthritis (RA) and an inadequate response to methotrexate. Bari, a selective Janus kinase 1/2 inhibitor, is approved for the treatment of moderate to severe active RA in adults in >50 countries. For improved treatment strategy, it is important to understand whether the pt population is composed of distinct pt groups with differing treatment responses and associated baseline characteristics. Objectives: To identify different treatment trajectories, based on CDAI improvement, in bari 4mg treated pts over 52 weeks; and examine the associated clinical disease measures, structural damage score and baseline characteristics. Methods: Growth Mixed Model (GMM), a novel latent class mixed model, was used to classify the longitudinal disease patterns instead of predefining a clinical responder at a specific time point. GMM was applied to observed CDAI values for bari 4mg pts, continuously treated from 0-52 weeks or up to rescue, to cluster pts into subgroups based on their trajectory patterns. Following identification of the groups, baseline pt characteristics and disease measures were compared between groups. Results: Bari 4mg treated pts (N=487) were classified into 3 groups based on their CDAI trajectory patterns: Group 1 (n=344, 71%), Group 2 (n=56, 11%), and Group 3 (n=87, 18%) (Figure). Group 1 had lower baseline CDAI (34, Table 1 ), achieved CDAI≤10 (low disease activity, LDA) rapidly and maintained LDA up to 52 weeks. Group 2 had higher CDAI at baseline (48, Table 1 ), responded quickly, and although pts took longer to attain LDA, they continued to show CDAI improvement. Group 3 had similar baseline CDAI values (48, Table 1 ) to Group 2 but higher baseline damage (mean total Sharp score [mTSS] of 50, versus 41 for Groups 1 and 2, Table 1 ). Most Group 3 pts did not achieve LDA but continued to show improvement over time. The majority of pts had no radiographic progression with the highest proportion in Group 1 (Table 2 ). The trajectories of average pain VAS, Health Assessment Questionnaire–Disability Index (HAQ-DI), tender joint count 28, and swollen joint count 28 were consistent in the 3 groups. W=week Conclusion: Baseline severity is associated with different treatment trajectories. With bari treatment, majority of pts achieved LDA and had no structural progression. Pts with high baseline disease activity were associated with longer time to achieve LDA. Pts with higher baseline structural damage in addition to high disease activity were less likely to achieve LDA, but consistent with the other groups, had similar low rate of joint damage progression. Long-term maintenance and continued improvement in CDAI were observed with bari treatment. Disclosure of Interests: Peter C. Taylor Grant/research support from: Celgene, Galapagos, Eli Lilly, UCB, Consultant for: AbbVie, Galapagos, Gilead, Eli Lilly, Pfizer Inc, Paul Emery Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, UCB, Roche, Novartis, Gilead, Samsung, Sandoz and Lilly, Michael E. Weinblatt Shareholder of: Stock option: CanFite, Lycera, Scipher, Inmedix, Grant/research support from: Crescendo Bioscience, Bristol Myers Squibb, Sanofi, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, CanFite, Corrona, Crescendo, GlaxoSmithKline, Gilead, Horizon, Lilly, Lycera, Merck, Novartis, Pfizer, Roche, Samsung, Scipher, Set Point, Eduardo Mysler Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Pfizer, Novartis, Janssen, Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lily, Janssen, Medimmune, Pfizer Inc, and Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lily, Janssen, Medimmune, Pfizer Inc, and Roche, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Pfizer, Novartis, Janssen, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lily, Janssen, Medimmune, Pfizer Inc, and Roche, Andrea Rubbert-Roth Consultant for: Chugai, Eli Lilly, Roche, and Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Hexal/Novartis, Janssen, Eli Lilly, Merck Sharp & Dohme, Pfizer, Roche, and Sanofi, Bochao Jia Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Luna Sun Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Yushi Liu Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Yun-Fei Chen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Anabela Cardoso Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics